Model for predicting long-term sinus rhythm retention after electrical cardioversion in patients with persistent atrial fibrillation. - K. O. Pysarevska; O. I. Zharinov (Medičnì Perspektivi)
The aim - to create a model for predicting long-term sinus rhythm retention after electrical cardioversion (ECV) based on individual patients characteristics. 141 patients with persistent AF who were planning to have sinus rhythm restoration, underwent general clinical examination, ECG and transthoracic echocardiographic. In 6 months after ECV patients were divided into two groups: 83 patients maintained sinus rhythm for 6 months (group I), recurrence of AF was observed in 58 patients (group II). The results of the ROC analysis determined statistically significant parameters that contribute to long-term retention of the sinus rhythm: non-modifiable (age, history and duration of the last episode of arrhythmia, combination of background diseases), modifiable (smoking, antiarrhythmic therapy, severity of heart failure by NYHA). A multifactorial prognostic model is created with the help of the modern approach of creating scorecards. This allowed in the form of a numerical characteristic to determine the probability of a long retention of the sinus rhythm. The selection of factors for the scoring model was in accordance with the criteria of the power of their influence on the retention of the sinus rhythm. The scoring model was created for predicting long-term retention of sinus rhythm after electrical cardioversion based on the individual characteristics of a patient with a persistent form of AF. The model has a high sensitivity (92.77%) and specificity (70.69%) and allows to predict the further course of the disease and to correct the therapy on time.